The Interaction Between Entrepreneurial Marketing, Social Capital, and Human Capital on Innovative Performance Among MSMEs - Siti Khotimah; Hendra Jayusman; M. Fatchurahman; Yanneri Elfa Kiswara Rahmantya; Darmono Darmono (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Micro, small, and medium enterprises (MSMEs) face increasing competition, digitalization, and changing consumer preferences, requiring them to strengthen innovation capabilities through entrepreneurial marketing, human capital, and social capital Objective: This study aims to analyze the effects of entrepreneurial marketing, social capital, and human capital on the innovative performance of micro, small, and medium enterprises (MSMEs) in Kotawaringin Barat. Methods: This research employed a quantitative approach with an explanatory survey design. Data were collected from 44 MSME actors and analyzed using SEM-PLS through SmartPLS 4.0. Entrepreneurial marketing served as the independent variable, innovative performance as the dependent variable, and social capital and human capital as moderating variables. Results: The results show that entrepreneurial marketing, social capital, and human capital have positive and significant effects on MSME innovative performance. Human capital was also found to strengthen the relationship between entrepreneurial marketing and innovative performance. Conversely, social capital was not proven to moderate this relationship. The interaction between human capital and social capital, as well as the three-way interaction among entrepreneurial marketing, social capital, and human capital, was also not significant. These findings indicate that MSME innovative performance is determined more strongly by the strength of entrepreneurial marketing strategies and the quality of business actors’ capacities. Conclusion: The implications of this study emphasize the importance of strengthening human resource capacity, developing entrepreneurial marketing, and utilizing social capital productively to enhance regional MSME innovation.